Role of periodontal pathogenic bacteria in RANKL-mediated bone destruction in periodontal disease - Kajiya, Mikihito; Giro, Gabriela [UNESP]; Taubman, Martin A.; Han, Xiaozhe; Mayer, Marcia P.A.; Kawai, Toshihisa (Taylor & Francis, 2010)
Accumulated lines of evidence suggest that hyperimmune responses to periodontal bacteria result in the destruction of periodontal connective tissue and alveolar bone. The etiological roles of periodontal bacteria in the onset and progression of periodontal disease (PD) are well documented. However, the mechanism underlying the engagement of periodontal bacteria in RANKL-mediated alveolar bone resorption remains unclear. Therefore, this review article addresses three critical subjects. First, we discuss earlier studies of immune intervention, ultimately leading to the identification of bacteria-reactive lymphocytes as the cellular source of osteoclast-induction factor lymphokine (now called RANKL) in the context of periodontal bone resorption. Next, we consider (1) the effects of periodontal bacteria on RANKL production from a variety of adaptive immune effector cells, as well as fibroblasts, in inflamed periodontal tissue and (2) the bifunctional roles (upregulation vs. downregulation) of LPS produced from periodontal bacteria in a RANKL-induced osteoclast-signal pathway. Future studies in these two areas could lead to new therapeutic approaches for the management of PD by down-modulating RANKL production and/or RANKL-mediated osteoclastogenesis in the context of host immune responses against periodontal pathogenic bacteria. © 2010 Mikihito Kajiya et al.
Keywords: Bone resorption; Osteoimmunology; Periodontal pathogenic bacteria; Rankl